Bağımsızlık öncesi ve sonrası Orta Asya’da Nakşibendilik: Hüseyniyye kolu örneğinde - İSABAEVA, Mairamkan (Scientific Journal of Faculty of Theology, 2023)
İslam is a whole. Therefore, all science branches which cover it are integrated in the same way with this whole. The main sources are certain. Other than that, there is a wreck lifestyle which has no a name in the beginning, but applied in every day life and it is the Sufism which is outlined. Sufism has been a science which has got diverses in its definition, it has been deeply dealt with the definition and lifestyle from the beginning. Sufism and sect are an integral part of each other. Sufism and sect complete each other at the same time. Naqshbandiyah has adopted itself as strong as the other sects. Especially it was occured in Transoxiana and then separated in the lands of Anatolia. It is being existed to our days. In our article we researched the Huseyniyye handle of Naqshbandiyah which is situated in Central Asia, in the lands of Kyrgyzstan, Kazakhstan and Uzbekistan. We researched the actions of that handle in the period of USSR and after the independence of the counted above countries. We fixed that the members of the Sect and murshids had lived between two countries, and near to boundaries, so they lived between three countries.